Інноваційно-орієнтований менеджмент в політиці сталого землекористування підприємств агропродовольчої сфери економіки - Лебедєва, Наталія Андріївна; Мартинюк, М. П.; Олійник, А. С.; Большакова, Є. Л. (My University, 2024)
У статті доведено, що інноваційно-орієнтований менеджмент землекористування підприємств агропродовольчої сфери є важливою складовою сталого розвитку. Воно означає раціональне використання земельних ресурсів з урахуванням екологічних, економічних та соціальних аспектів. Обгрунтовано, що ефективне землекористування допомагає забезпечити оптимальне розташування та використання земельних площ, мінімізувати негативний впливна довкілля, підвищити врожайність та якість сільськогосподарських культур, та забезпечити стабільний розвиток сільського господарства та суспільства в цілому. Запропоновані такі заходи, як впровадження сучасних сільськогосподарських технологій, раціональне планування земельних угідь, охорона грунтів та водних ресурсів,збалансований підхід до використання земель для різних цілей. Доведено, що основною метою ефективного землекористування є досягнення балансу між господарськими потребами та збереженням природних екосистем для майбутніх поколінь. The article proves that innovationLoriented land use management of agroLfood enterprises is an important componentof sustainable development. It means rational use of land resources taking into account ecological, economic and socialaspects. It is substantiated that effective land use helps to ensure the optimal location and use of land areas, minimize thenegative impact on the environment, increase the yield and quality of agricultural crops, and ensure the stable developmentof agriculture and society as a whole. Optimizing land use is an important aspect of sustainable development. Its purposeis to ensure optimal use of land resources, taking into account natural and anthropogenic factors. This process is carriedout through the establishment of an effective connection between the land and the environment. Scientific literaturedefines the optimization of land use as the organization of the production process, which allows achieving the rationaluse of land with maximum productivity and environmental sustainability. The main goal of optimization is to achieveeffective management of land resources, which ensures the preservation of soil fertility and ecologically sustainabledevelopment. Such measures as the introduction of modern agricultural technologies, rational land planning, protectionof soil and water resources, a balanced approach to the use of land for various purposes are proposed. It has been proventhat the main goal of effective land use is to achieve a balance between economic needs and the preservation of naturalecosystems for future generations. InnovationLoriented management of the efficiency of land use really plays a key rolein the development of the state's economy and meeting the socioLeconomic needs of society. This means that the use andreproduction of land must be properly regulated and controlled by economic entities. In the context of digitalization andlogistical threats, organizational and membership levers, as well as tools, play an important role in ensuring thecompetitive development of agroLindustrial production. Digitalization can facilitate the introduction of new technologiesand approaches to land use management, improving logistics and production efficiency.
Інноваційно-орієнтований менеджмент в політиці сталого землекористування підприємств агропродовольчої сфери економіки / М. П. Мартинюк, А. С. Олійник, Н. А. Лебедєва, Є. Л. Большакова // АГРОСВІТ. - 2024. - № 4. - С. 72-79. - Режим доступу: DOI: 10.32702/2306-6792.2024.4.72
Keywords: підприємства агропродовольчої сфери; оптимізація землекористування; ста=лий розвиток; інноваційно=орієнтований менеджмент; механізм управління; політика стало=го землекористування; економіка; agro=food enterprises; land use optimization; sustainable development; innovation=oriented management; management mechanism; sustainable land use policy; economics